VCAST: Scalable Dissemination of Vehicular Information with Distance-Sensitive Precision. (4th November 2013) - Kulathumani, V.; Moparthi, R. A.; Fallah, Y. P.
Abstract : Real-time information about the state (location, speed, and direction) of other vehicles in the system is critical for both safety and navigation applications in future intelligent transportation systems. However, reliably obtaining this information over multiple hops in a capacity constrained, contention-prone wireless network poses a significant challenge. In this paper, we describe an algorithm VCAST that addresses this challenge by exploiting a notion of distance sensitivity in information propagation, in which information is forwarded at a rate that decreases linearly with distance from the source. By doing so, the required communication overhead per node can be significantly reduced, thereby reducing channel contention, allowing higher information supply rates, and scaling to larger network sizes. VCAST can be used to improve safety against collisions and to enable dynamic routing and navigation techniques by providing aggregate traffic information in an extended neighborhood. The performance of VCAST is validated using extensive ns-3 simulations under different network sizes and densities with an IEEE 802.11b transmission model and the advantages of VCAST in comparison to non-distance-sensitive approaches are highlighted.